Reversal of loop ileostomy under an Enhanced Recovery Programme – Is the stapled anastomosis technique still better than the handsewn technique?. (November 2015) - Markides, G.A.; Wijetunga, I.; McMahon, M.; Gupta, P.; Subramanian, A.; Anwar, S.
Abstract: Introduction: Recent literature suggests that stapled anastomotic (SA) technique for the reversal of loop ileostomy (LI) may be beneficial in terms of early recovery and reduced incidence of small bowel obstruction when compared to the handsewn anastomosis (HA). Enhanced Recovery Programme (ERP) after colorectal procedures has demonstrated a reduction in some aspects of surgical morbidity. The aim of this study was to investigate the outcomes of patients undergoing reversal of LI within an ERP programme and compare the HA to the SA in relation to clinical outcomes. Material and methods: All adult patients undergoing elective reversal of loop ileostomy between January 2008 and December 2012 without any additional procedures, were included in our study. Adherence to ERP modules and 30 day postoperative complications were assessed via retrospective review of patient case notes. Results: One hundred and eight patients had an ileostomy reversal; 61 in the SA and 47 in the HA group. There were no demographic differences between the two groups. ERP module compliance was satisfactory (>80%) in 11 of the 14 modules with no difference in individual module compliance between the two groups. The operating times were found to be comparable (p = 0.35). Overall mortality (p = 0.44), anastomotic leak rates (p = 1.00), intra-abdominal collections (p = 0.65), small bowel obstruction (p = 1.00), reoperation rates (p = 0.65), ileus (p = 0.14) and other significant complications (Clavien-Dindo > 2) (p = 0.08) were similar between the two groups. A significantly longer total length of hospital stay (TLOS) was found in the SA group (median 3 Vs 4 days, p = 0.009). Conclusion: Reversal of LI under an ERP appears to potentially neutralise the suggested SA benefits in terms of postoperative complications without any additional negative implications. Other non-operative factors may have a potential effect on outcomes such as the TLOS. Highlights: The reversal of loop Ileostomy can be carried out either by stapled anastomosis or a hand-sewn technique. Literature suggests that stapled reversal has advantages over the hand-sewn technique in terms of reduced ileus and early postoperative recovery. Our study has challenged this historical data by comparing the two techniques under the newly implemented Enhanced Recovery Programme (ERP). When patients are recovered under ERP there is no additional benefit to stapled reversal technique in terms of post op. recovery and complications.